The Impact of IFRS 9 on the Link Between Lending and the Capital Ratio in Publicly Traded Banks in Poland - Paweł Bojar; Małgorzata Anna Olszak (Journal of Banking and Financial Economics)
This paper aims to determine the role of the expected credit loss approach as defined in IFRS 9 in the effects of capital ratio on loans growth in publicly traded banks in Poland. To resolve this problem, we apply semi-annual data of individual banks in 2012–2018. Using several estimation techniques, we find that in the period of implementation of the expected credit loss approach, the links between loans growth and the capital ratio were enhanced. In particular, lending growth is more sensitive to levels of the capital ratio. These results are important with respect to the goal of bank financial stability and have implications for the conduct of macroprudential policy.